PENGARUH STRATEGI PROMOSI TERHADAP VOLUME PENJUALAN TABUNGAN DI PT. BANK SUMUT CABANG PEMBANTU SYARIAH PANYABUNGAN - Windari, Windari (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
The background of the problem in this study is the promotion carried out by PT. Bank SUMUT Sharia Sub-branch is not optimal so saving a little and fewer transactions occur. The formulation of the research problem is whether there is a development strategy towards the savings sales volume? The purpose of this study was to study the effect of promotional strategies on savings sales volume. The theory used is the theory of promotion strategy on savings sales volume while the promotion strategy is carried out with four types of promotions, namely: advertising, personal sales, sales promotions, and publicity. Thus the strategy can increase the sales volume of savings. This research is quantitative research. The data source used is primary data. The technique of collecting data used was a questionnaire, with a total sample of 96 incomes. The analytical tool used is descriptive test, validity test, reliability test, normality test, simple linear regression analysis, hypothesis testing (t test), and R square test (r2). By using the SPSS Version 21.0 program. Obtained results obtained by Composition = 6.517 + 0.478X and the average R square of 0.472 or 47.2% promotion strategy variables are able to explain the sales volume variable with a total of 52.8% variable variables that cannot be discussed in this model ( not approved) . Hypothesis test results (t test) state that t count t table (9,164 1,985) and the significance level obtained is 0,000 α (0,14) then Ha is accepted. The importance of promotional strategies has a significant impact on savings sales volume. Keywords: Promotion, Strategy, Sales Volume